Isomerization of fatty acids: A cellular barrier mechanism in nanotechnology? - González Paz, Rodolfo (2017)
This work is a kinetic study of the coupling reaction of 2-mercaptoethanol with methyl undecenoate and with methyl oleate through " click " chemistry. Reversibility and reactivity of each system were followed through Fourier Transform Infrared Spectroscopy and ATR conversion (FTIR-ATR) and Nuclear Magnetic Resonance Spectroscopy (1 H NMR). It was proved that the addition of thiol to the alkene may be reversible, that it depends on factors such as the structure of the alkene and the concentration of thiol or photoinitiator, but that it is mainly affected by the isomerization process in fatty acids and the reactivity of each configuration (cis or trans). It was concluded that under our " click " chemical experimental conditions, the cis form of methyl oleate is more reactive than the trans form. Finally, the plausibility of applying this process in nanotechnology is discussed as a cellular barrier mechanism to avoid internalization of toxic nanoparticles